2018
DOI: 10.1186/s12917-018-1523-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to identifying and quantifying neutrophil extracellular trap formation in septic dogs using immunofluorescence microscopy

Abstract: BackgroundCanine neutrophils release neutrophil extracellular traps (NETs) in response to lipopolysaccharide but NETs from clinical septic dogs had not been identified. The primary aim is to describe the methodology of identifying and quantifying neutrophil extracellular traps (NETs) in cytology samples of septic foci in dogs with sepsis using immunofluorescence microscopy. Cytology samples including endotracheal tracheal wash (ETW), bronchoalveolar lavage (BAL), abdominal and pleural effusion collected from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…It could also suggest that adaptive immune responses and collaborative interactions between leukocytes reacting to the presence of bacteria leads to a distinct, or a greater inflammatory response than tissue damage alone. The high concentrations of cfDNA and nucleosomes in the peritoneal effusions of SP dogs is also very suggestive that NET release was occurring in the peritoneal cavities of these dogs, as has been previously reported (89). The increased blood PCT concentrations relative to those in effusion identified in the present study is consistent with previous findings of high PCT concentrations in dogs with sepsis (20, 21).…”
Section: Discussionsupporting
confidence: 82%
“…It could also suggest that adaptive immune responses and collaborative interactions between leukocytes reacting to the presence of bacteria leads to a distinct, or a greater inflammatory response than tissue damage alone. The high concentrations of cfDNA and nucleosomes in the peritoneal effusions of SP dogs is also very suggestive that NET release was occurring in the peritoneal cavities of these dogs, as has been previously reported (89). The increased blood PCT concentrations relative to those in effusion identified in the present study is consistent with previous findings of high PCT concentrations in dogs with sepsis (20, 21).…”
Section: Discussionsupporting
confidence: 82%
“…NETs have been detected in bronchoalveolar lavage samples from septic humans or canines with ARDS, indicating that, even after transmigration, neutrophils are capable of undergoing NETosis (174, 175). A recent study utilizing samples from different models of ALI in mice and from patients with ALI revealed increased levels of NETs and histones H3 and H4 in the bronchoalveolar lavage fluids (BALF) (176).…”
Section: Detrimental Effects Of Nets In Sepsismentioning
confidence: 99%
“…For example, Streptococcus pneumoniae , a Gram-positive bacteria commonly found in the human respiratory tract, can express the virulence factor, endA, which degrades DNA, allowing for bacteremia and sepsis to occur ( 71 ). We recently demonstrated that NETs within the septic foci of clinical septic dogs can bind directly to bacteria suggesting that entrapment of bacteria by NETs may occur in dogs (Figures 1B,C ) ( 72 ).…”
Section: Beneficial Role Of Nets In Sepsismentioning
confidence: 98%
“…Migration of neutrophils from the vasculature into the interstitium and bronchoalveolar space is a key feature of ARDS in sepsis. NETs in bronchoalveolar lavage fluid collected from septic people and dogs with ARDS have recently been documented indicating that transmigrated neutrophils undergo NETosis in naturally occurring ARDS ( 56 , 57 , 72 , 92 ). Serine proteases released via NETosis can have a direct pathophysiological role in the progression of ARDS.…”
Section: Detrimental Role Of Nets In Sepsismentioning
confidence: 99%